Adsorption Characteristics of Acid Dyes by the Live Activated Sludge - Basibuyuk, Mesut (Asian Journal of Chemistry, 2010)
Adsorption is the one of the aspects of abiotic removal and in current work, the adsorption properties of two acid dyes by live activated sludge were examined in a batch system. The dyes tested for the adsorption by live activated sludge were Lanaset yellow 4GN and Lanaset red G. Both acid dyes adsorbed by the live activated sludge to some degree and the equilibrium was obtained with in 160 min. The data obtained from equilibrium studies fit to both Langmuir and Freundlich models. Based on the Langmuir model, qmax values were found 69.48 and 144.91 mg/g for Lanaset yellow 4GN and Lanaset red G, respectively. Gibbs free energies of adsorption were also calculated and negative values were found for each dye and sludge system. Intraparticle diffusion was found significant for both dyes tested and overall adsorption process was best described by pseudo second order model. Rate constants for each of the model were also calculated.